The Onset of a Globally Ice‐Covered State for a Land Planet. Issue 12 (28th November 2021) - Kodama, T.; Genda, H.; Leconte, J.; Abe‐Ouchi, A.
Abstract: The climates of terrestrial planets with a small amount of water on their surface, called land planets, are significantly different from the climates of planets having a large amount of surface water. Land planets have a higher runaway greenhouse threshold than aqua planets, which extends the inner edge of the habitable zone inward. Land planets also have the advantage of avoiding global freezing due to drier tropics, leading to a lower planetary albedo. In this study, we systematically investigate the complete freezing limit for various surface water distributions using a three‐dimensional dynamic atmospheric model. As in a previous study, we found that a land planet climate has dry tropics that result in less snow and fewer clouds. The complete freezing limit decreases from that for aqua planets (92% S 0, where S 0 is Earth's present insolation) to that for land planets (77% S 0 ) with an increasing dry area. Values for the complete freezing limit for zonally uniform surface water distributions are consistently lower than those for meridionally uniform surface water distribution. This is because the surface water distribution in the tropics in the meridionally uniform cases causes ice‐albedo feedback until a planet lapses into the complete freezing state. For a surface water distribution using the topographies of the terrestrial planets, the complete freezing limit has values near those for the meridionally uniform cases. Our results indicate that the water distribution is important for the onset of a global ice‐covered state for Earth‐like exoplanets. Plain Language Summary: Some exoplanets are thought to be Earth‐like rocky planets within the habitable zone, where liquid water is stable on the planetary surface. Land planets with a small amount of surface water have the advantage of maintaining liquid water on their surface. We investigated the complete freezing limit using a three‐dimensional general circulation model assuming various surface water distributions. The insolations at the complete freezing limit gradually decrease from that for a water‐rich planet to that for a dry planet with an increasing dry area. Our results showed that the amount of water significantly affects the initiation of a global ice‐covered state for Earth‐like exoplanets. Key Points: The onset of a globally ice‐covered state becomes lower as the area of dry region increases At lower insolation, land planets are warmer than aqua planets because of less cloud and snow which lead to lower planetary albedo The surface water distribution is one of the keys to determining the complete freezing limit